Effect of Set Size and Fertilizer Type on Off- Season Onion (Allium cepa. L) Production - E. E. Elshukry Elsadig; Z. Elhag Ayoub; A. Mohammedali Aisha (Journal of Agronomy Research, 2022)
Two off-season experiments were conducted during 2015/16 and 2017/18 at Shambat Research Station Farm, Khartoum, Sudan, to investigate the effects of large (2-3 cm) and small (1-2 cm) sets size of onion variety Baftaim (S) and two chemical fertilizer (Urea 240 kg/ha) and NPK(15:15:15) (120 kg/ha) in addition to organic fertilizer (Elkhaseeb 20 tons/ha) and their combinations (Urea+ Elkhaseeb and NPK+Elkhaseeb) on off-season production. The experimental units were in split plot design, with set size and fertilizers as main and sub plots, respectively, with three replications. The yield was evaluated as bulb weight and yield/ha, whereas, the quality was evaluated as marketable and percentage of double and bolted bulbs, TSS and dry matter. The results reflected no significant differences in bulb weight due to set size, fertilizer type and their interactions, however, the heaviest bulbs were obtained by Elkhaseeb + urea and its interaction with the large set size in both seasons. The small set size gave the highest yield, organic fertilizer (Elkhaseeb) alone or in combination with urea gave the highest yield, whereas, the lowest one was obtained with the combination of organic fertilizer with N P K. The bulb quality was also affected by set size and fertilizer type as the highest marketable yield was obtained by small set size and fertilizer combination (organic + urea) or urea alone. No significant effects on TSS and dry matter percentage due to set size, fertilizer type and their interactions were noticed. The highest marketable yield, TSS and dry matter were obtained by Elkhaseeb (organic fertilizer) with mineral fertilizers (urea or NPK) with the small set size rather than organic or mineral fertilizer alone. It could be concluded and recommended that onion set size of about 1-2cm diameter with an organic - mineral fertilizer combination could improve off-season onion yield and quality. However, further studies are required to find the proper fertilizers dose.
Keywords: fertilizer